Carbon dots self-decorated heteroatom-doped porous carbon with superior electrocatalytic activity for oxygen reduction. (1st March 2020) - Liang, Kaixin; Wang, Liqiang; Xu, Ying; Fang, Yong; Fang, Yin; Xia, Wei; Liu, You-Nian
Abstract: Developing advanced carbon materials as a metal-free electrocatalyst to replace noble metal-based one for, but not limited to, oxygen reduction reaction (ORR) is of great allure but remains challenging. In this work, carbon dots (CDs) self-decorated, N, S codoped porous carbon (NSPC) was fabricated by alkali-assisted protein decomposition and reconstruction. Specifically, in hot alkaline solution, proteins hydrolyzed into protein fragments, and then part of the fragments formed highly crystalline CDs. After freeze-dried and pyrolyzed, the CDs-containing protein fragments were converted into CDs/NSPC composites. The as-prepared CDs/NSPC possesses rich edge, heteroatom-dopant, high porosity, and smooth electron transfer between CDs and NSPC, synergistically contributing to CDs/NSPC such an outstanding ORR catalytic performance that even outperforms Pt/C. Furthermore, CDs/NSPC was evaluated as an air electrode catalyst for Zn-air batteries with excellent stability and high-power density. Graphical abstract: Image 1